Elevated urinary transforming growth factor-beta1 level as a tumour marker and predictor of poor survival in cirrhotic hepatocellular carcinoma. - Tsai, J. F. (Nature Publishing Group, 1997)
To assess the clinical relevance of transforming growth factor-beta1 (TGF-beta1) in hepatocellular carcinoma (HCC), urinary TGF-beta1 and serum alpha-fetoprotein (AFP) were determined in 94 patients with cirrhotic HCC, 94 age- and sex-matched patients with cirrhosis alone and 50 healthy adults. TGF-beta1 level in HCC was higher than in cirrhosis alone or in healthy controls (each P = 0.0001). There is an inverse correlation between TGF-beta1 and AFP levels (r = -0.292, P = 0.004). Significantly higher TGF-beta1 level was found in HCC patients with worsening Child-Pugh stages, diffuse HCC, tumour size > 3 cm, multilobular tumour and AFP < or = 20 ng ml(-1). TGF-beta1 level decreased after complete treatment with transcatheter arterial chemoembolization (P = 0.0001). The median survival in HCC patients with raised TGF-beta1 was shorter than those with normal TGF-beta1 (P = 0.018). Multivariate analysis indicated that TGF-beta1 and AFP were significantly correlated with the presence of HCC. In addition, TGF-beta1 could be used as a diagnostic marker for HCC, particularly in tumours with low AFP production. In conclusion, elevated urinary TGF-beta1 level is a tumour marker and predictor of poor survival for cirrhotic HCC.